2014
DOI: 10.1101/lm.035972.114
|View full text |Cite
|
Sign up to set email alerts
|

Long-term potentiation can be induced in the CA1 region of hippocampus in the absence of αCaMKII T286-autophosphorylation

Abstract: a-calcium/calmodulin-dependent protein kinase (aCaMKII) T286-autophosphorylation provides a short-term molecular memory that was thought to be required for LTP and for learning and memory. However, it has been shown that learning can occur in aCaMKII-T286A mutant mice after a massed training protocol. This raises the question of whether there might be a form of LTP in these mice that can occur without T286 autophosphorylation. In this study, we confirmed that in CA1 pyramidal cells, LTP induced in acute hippoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 95 publications
(111 reference statements)
0
11
1
Order By: Relevance
“…However, when we applied high frequency synaptic stimulation (40 Hz, 15 s; corresponding to ~8 Hz glutamate uncaging), LTP in Camk2a T286A mice was rescued (ΔEPSC = 76 ± 20%; Figure 4H, 4I). LTP induced by 40 Hz stimulation was abolished by the NMDAR antagonist APV, suggesting it is NMDAR-dependent (Figure S6A, S6B), unlike some other forms of LTP (Villers et al, 2014). To confirm that LTP induced by 40 Hz synaptic stimulation is CaMKII-dependent, we co-injected AAV encoding Cre and floxed-tdTM to the lateral ventricle of Camk2a fl/fl embryos.…”
Section: Resultsmentioning
confidence: 92%
“…However, when we applied high frequency synaptic stimulation (40 Hz, 15 s; corresponding to ~8 Hz glutamate uncaging), LTP in Camk2a T286A mice was rescued (ΔEPSC = 76 ± 20%; Figure 4H, 4I). LTP induced by 40 Hz stimulation was abolished by the NMDAR antagonist APV, suggesting it is NMDAR-dependent (Figure S6A, S6B), unlike some other forms of LTP (Villers et al, 2014). To confirm that LTP induced by 40 Hz synaptic stimulation is CaMKII-dependent, we co-injected AAV encoding Cre and floxed-tdTM to the lateral ventricle of Camk2a fl/fl embryos.…”
Section: Resultsmentioning
confidence: 92%
“…However, they only follow maintenance for short periods. Other work using the same mutation (Villers et al, 2014) measured LTP over longer periods and found that normal LTP was not maintained but, rather, was replaced by a form of potentiation that does not have synapse specificity or NMDAR dependence. In summary, the model of (Chang et al, 2017; Murakoshi et al, 2017) leaves a large number of experimental results demonstrating long-lasting changes in CaMKII unexplained (Ahmed and Frey, 2005; Fukunaga et al, 1993; Lengyel et al, 2004; Otmakhov et al, 2004) and is inconsistent with results showing that manipulations of CaMKII during the maintenance period can affect LTP (Barcomb et al, 2016; Sanhueza et al, 2011) and behavior (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of CaMKII leads to enhance-ment of synaptic transmission, and LTP is occluded by increasing the concentrations of constitutively active CaMKII (Pettit et al 1994). The role of CaMKII as a synaptic tag that mediates synapse-specific LTP has been shown in hippocampal CA1 of ␣CaMKII-T286A mutant mice (Villers et al 2014). Several forms of LTP can be induced in these mice but at the expense of synaptic input specificity.…”
mentioning
confidence: 99%
“…Several forms of LTP can be induced in these mice but at the expense of synaptic input specificity. In the absence of ␣CaMKII autophosphorylation, LTP is not restricted to stimulated synapses (Villers et al 2014). However, the role of CaMKII in the stimulus specificity of natural learning and memory has not been addressed explicitly.…”
mentioning
confidence: 99%